A novel type of acyclic nucleoside phosphonates derived from 2-(phosphonomethoxy)propanoic acid - Kaiser, Martin Maxmilian; Jansa, Petr; Dračínský, Martin; Janeba, Zlatko (Tetrahedron, 2012)
A convenient and efficient synthesis of a novel class of acyclic nucleoside phosphonates derived from 2-(phosphonomethoxy)propanoic acid has been developed. The key step of the synthesis is the optimized oxidation of the 3-hydroxy-2-(phosphonomethoxy)propyl (HPMP) analogues to the corresponding 2'-carboxy-PME (CPME) derivatives using the TEMPO/NaClO2/NaClO oxidizing system. Although (S)-3-(adenin-9-yl)-2-(phosphonomethoxy)propanoic acid ((S)-CPMEA) has been designed as a compound with potential anti-HIV activity, none of the newly prepared CPME analogues exhibited any antiviral activity.
Keywords: Oxidation; PMEA; CPMEA; Antiviral; Acyclic nucleoside phosphonates; Microwave; TEMPO; HPMPA